Prevalence of depression in PLHA attending ART centre of Assam medical college and hospital, Dibrugarh - Kotoky, Manas Jyoti; Gogoi, Gourangie (International Journal Of Community Medicine And Public Health, 2017)
Background: Depression is a common mental health disorder encountered in people living with HIV/AIDS. Depression has a strong impact on the daily chores in the lives of those suffering from HIV/AIDS and their ability to cope with the disease and has a special role to play in adherence to antiretroviral therapy. This study was undertaken to assess the prevalence of depression in PLHA attending the ART centre of AMCH. Methods: A cross sectional study was carried out on 54 patients attending the ART centre. They were interviewed using a predesigned and pretested proforma with prior consent. Depression was assessed using the MDI-4 scale and data was analysed using SPSSv16. Chi square test was done to see the association. Results: Majority (85%) of the respondents were male. Prevalence of depression was found in 55.6% of the respondents. Alcoholic history was found in 54% and smoking in 24% (p<0.05). Most were educated below 10th grade (66.6%) (p<0.05). Most of them (83.3%) disclosed their status to their family members. Conclusions: The prevalence of depression is very high in PLHA. To diagnose depression and to treat at the earliest will go a long way in improving their quality of life.